2014
DOI: 10.1088/1367-2630/16/7/073009
|View full text |Cite
|
Sign up to set email alerts
|

Thermal instability of cell nuclei

Abstract: DNA is known to be a mechanically and thermally stable structure. In its double stranded form it is densely packed within the cell nucleus and is thermo-resistant up to°70 C. In contrast, we found a sudden loss of cell nuclei integrity at relatively moderate temperatures ranging from 45 to°55 C. In our study, suspended cells held in an optical double beam trap were heated under controlled conditions while monitoring the nuclear shape. At specific critical temperatures, an irreversible sudden shape transition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 64 publications
2
15
0
Order By: Relevance
“…Several papers already proved that cell optical deformability allows distinguishing healthy, tumorigenic and metastatic cells, and also showed that optical stretching can be used to reveal the effects of drug treatments on the mechanical response of the cell 5 17 22 34 . Additionally, a series of recent papers exploits the optical stretcher as a tool to study the effect of temperature on cell mechanics to better understand cellular thermorheology 35 36 37 38 .…”
mentioning
confidence: 99%
“…Several papers already proved that cell optical deformability allows distinguishing healthy, tumorigenic and metastatic cells, and also showed that optical stretching can be used to reveal the effects of drug treatments on the mechanical response of the cell 5 17 22 34 . Additionally, a series of recent papers exploits the optical stretcher as a tool to study the effect of temperature on cell mechanics to better understand cellular thermorheology 35 36 37 38 .…”
mentioning
confidence: 99%
“…The strain response for small laser powers shows a more pronounced viscous response, whereas for high laser powers a more viscoelastic response is distinguishable. However, the initial rapid, irregular deformation, between 1 and 1.5 s, is partially a result of the nuclear thermal instability of the MCF-7 cells [55]. Since we further investigate the cytoskeletal effects of toxins, the induced constant offset in the relative deformation due to nuclear reshaping is not an essential issue in further data analysis.…”
Section: Resultsmentioning
confidence: 99%
“…We designed the setup in a minimalistic approach to change as few parameters as possible to keep the systems comparable. In this regard, we used the same lasers, optical fibers, and reservoirs as in previous studies concerning cancer research [4,8,39,59,60], various research questions of single cell rheology [38,40,41,61,62], and the principle of the Optical Stretcher as an optical rheometer for living cells [36,37,50]. The microfluidic surroundings have been adopted as far as possible, keeping the channel dimensions and path lengths, as well as flow velocities and pressure in the same order of magnitude.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, forces in the pN range are sufficient to induce relatively large deformations, which can be readily detected and quantified. Employing higher laser powers to achieve larger deformation forces is accompanied with the risk of damaging the cells due to heat shock, resulting in an unambiguous mechanical fingerprint [50,61]. However, the pN force regime is sufficient to investigate cell mechanics and even allows to record multiple deformation processes.…”
Section: Resultsmentioning
confidence: 99%